STRATEGI KONVERSI ENERGI DI PT. LION METAL WORKS Tbk. - Daud Sudradjad; Mahfud MS; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2009)
PT Lion Metal Works is a company producing office equipment, racking system, building material, security and fireproof safe, and cold forming. The production activity has high dependence on the usage of diesel, which influences the quality of the product and the cost of total business. The price fluctuation is one of the reasons for the company to convert the usage of diesel to some energy alternatives. Gas is the best alternative to replace diesel due to some advantages such as price, installation cost, distribution issue, calorie level, and environmental issue. There are some resistances from internal organization emerge in the implementation of the conversion. The alternatives strategy has been explored to reduce the resistances considering the goal of the organization, the actors (department in the company), and the type of resistance using analytical hierarchy process method. The priority strategy is establishing a new division for handling the conversion program and installing the gas facility gradually.